Utilização de um eletrodo de grafite-epóxi recoberto com [Zn(FEN)3][tetratris(4-clorofenil) borato]2 sensível a zinco(II) em meio 1,10-fenantrolina como eletrodo indicador em titulações potenciométricas de precipitação - Teixeira, Marcos F. S. [UNESP]; Fatibello-Filho, Orlando; Ramos, Luiz Antônio (Sociedade Brasileira de Química, 2005)
The construction and analytical evaluation of a coated graphite-epoxy electrode sensitive to the zinc-1,10-phenantroline complex based on the [Zn(fen)3][tetrakis(4-chlorophenyl)borate]2 incorporated into a poly(vinylchloride) (PVC) matrix are described. A thin membrane film of this ion-pair, dibutylphthalate (DBPh) and PVC were deposited directly onto an electrically conductive graphite-epoxy support located inside a Perspex® tube. The best PVC polymeric membrane contains 65% (m/m) DBPh, 30% (m/m) PVC and 5% (m/m) of the ion-pair. This electrode shows a response of 19.5 mV dec-1 over the zinc(II) concentration range of 1.0 x 10-5 to 1.0 x 10-3 mol L-1 in 1,10-phenantroline medium, at pH 6.0. The response time was less than 20 seconds and the lifetime of this electrode was more than four months (over 1200 determinations by each polymeric membrane). It was successfully used as an indicator electrode in the potentiometric precipitation titration of zinc(II) ions.
Utilization of a [Zn(FEN)3][tetrakis(4-chlorophenyl) borate]2 coated-graphite zinc(II) ion-selective electrode in 1,10-phenantroline medium as indicator electrode in potenciometric precipitation titrations
Keywords: zinc determination; zinc-ion selective electrode; potentiometric precipitation titrations